2009
DOI: 10.1111/j.1468-2389.2009.00472.x
|View full text |Cite
|
Sign up to set email alerts
|

Rating Level and Accuracy as a Function of Rater Personality

Abstract: We investigated the predictability of rating level and two measures of rating accuracy from rater Agreeableness (A) and Conscientiousness (C) scores of the Five Factor Model. One hundred and twenty-six students made peer ratings after participating in several group exercises under conditions designed to emulate the modal peer rating system in which raters had low accountability for their ratings. Scores were correlated with average rating level (r ¼.18, po.05) and both measures of rating accuracy (po.05) and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
61
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(73 citation statements)
references
References 43 publications
(88 reference statements)
9
61
0
1
Order By: Relevance
“…High-agreeableness individuals have shown a particular propensity to be motivated to give lenient ratings (Bernardin, Cooke, Ross & Villanova, 2000;Jawahar, 2001) perhaps because they value conflict-free, harmonious relationships with others and have a willingness to compromise their own interests for the sake of others (Goldberg, 1992). When combined with low rater conscientiousness, high agreeableness has been found to result in particularly lenient ratings (Bernardin, Tyler, & Villanova, 2009). …”
Section: Rater Agreeableness and Rating Context As Causes Of Leniencymentioning
confidence: 99%
See 2 more Smart Citations
“…High-agreeableness individuals have shown a particular propensity to be motivated to give lenient ratings (Bernardin, Cooke, Ross & Villanova, 2000;Jawahar, 2001) perhaps because they value conflict-free, harmonious relationships with others and have a willingness to compromise their own interests for the sake of others (Goldberg, 1992). When combined with low rater conscientiousness, high agreeableness has been found to result in particularly lenient ratings (Bernardin, Tyler, & Villanova, 2009). …”
Section: Rater Agreeableness and Rating Context As Causes Of Leniencymentioning
confidence: 99%
“…It has been shown that raters are not always willing to rate accurately: Managers can make accurate private judgments of employee performance but that these may not be the same as the ratings they give in public (Murphy & Cleveland, 1995;Tziner, Murphy, & Cleveland, 2005). This could cause particularly serious problems when poor work performance needs to be identified and discussed (Arvey & Murphy, 1998;Bernardin, Tyler, & Villanova, 2009;Heslin, Latham, & VandeWalle, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This measure could be examined as a state measure (influenced by the ratee and rating environment), a trait measure (a relatively stable attribute of the rater), or both. With regard to traits, Bernardin et al (2009) raters who were high on agreeableness and low on conscientiousness were also especially likely to be lenient in their PA. Other rater traits and rater states could be investigated in the context of an organizational environment that elicits or constrains trait-relevant behaviors (see the trait activation theory of Tett & Burnett, 2003).…”
Section: Social Context Of Organizations Affects Performance Managementmentioning
confidence: 99%
“…Such interventions might have main effects across all raters or might interact with individual differences in rater characteristics. For example, absent any formal intervention, conscientious raters generally tend to provide less lenient and more accurate ratings (e.g., Bernardin, Tyler, & Villanova, 2009), and in some cases, these raters seem to be less influenced by contextual demands that are consistent with conscientiousness (e.g., accountability to audience; Roch, Ayman, Newhouse, & Harris, 2005). Conversely, these interventions might be most effective in those raters who are especially susceptible to rating leniency.…”
Section: Social Context Of Organizations Affects Performance Managementmentioning
confidence: 99%